Strategies to Promote the Inclusion of Young Adults With Developmental Disabilities in Community-Based Health Studies. (June 2019) - Vazquez, Luz Maria; Khanlou, Nazilla; Davidson, Deborah; Aidarus, Fatma
We discuss strategies to promote the inclusion of people with developmental disabilities (DDs) in qualitative community-based research studies. Strategies were applied in three projects conducted between 2012 and 2017 that addressed issues of socioeconomic challenges, discrimination, and exclusion of children and young adults with developmental disabilities (YADD). Strategies included partnership with community organizations; inclusion of YADD, family caregivers (FCs), and service providers in advisory committees (ACs); and strategies to accommodate YADD. As part of our contribution, we discuss issues of invisibility and exclusion of individuals with DDs who have "low" functioning capacities. There is a need to review studies sampling inclusion criteria as they may constitute a barrier for participation. Preference for sampling "high" functioning individuals may reinforce exclusion in research, and replicate broader patterns of socioeconomic exclusion of individuals with disabilities. Our discussion of inclusive research is informed by critical disability studies and the underlying principle "nothing about us without us."